Case Report: A rare case of cervical lymph node metastasis from prostate cancer suspicious for combined lung cancer - Zhou, Fei-Yan; Du, Yue; Song, Fang-Hua; Sun, Jing-Yang (Frontiers in Oncology, 2025)
Cervical lymph node metastasis as the initial manifestation of prostate cancer is uncommon, and the diagnostic and therapeutic processes become considerably more complex when primary lung malignancy is also suspected. Immunohistochemical (IHC) techniques are critical in the diagnosis of multiple primary malignancies, in particular when histopathologic access is limited. We report on a 74-year-old male patient who presented with respiratory symptoms. Computed tomography revealed a 6.4-cm × 4.7-cm mass in the upper lobe of the right lung with cervical lymph node metastasis. The initial diagnosis of metastatic adenocarcinoma was established by cervical lymph node biopsy. During follow-up, the patient developed progressive dysuria, and prostate cancer was ultimately confirmed by prostate biopsy. IHC analysis of the cervical lymph node specimen revealed the following profile: prostate-specific antigen (PSA) (focally positive, 3+), P504S (diffusely positive, 3+), TTF1 (−), CK7 (−), CK20 (−), napsin A (−), and P40 (−). This IHC profile definitively established the prostatic origin of the metastatic carcinoma in the cervical lymph node. This case highlights the value of employing therapeutic diagnostic strategies when definitive histopathologic access is challenging and provides insights into the management of atypical metastatic prostate cancer and multiple primary cancers.